The Effect of Dettol Soap Television Advertisment to Gender Myth Through Semiotics - Tiarma Ika Yuliana; Astri Indriana Octavita Haryanto; Rima Novia Ulfa (Candradimuka: Journal of Education, 2023)
Advertisement is a form of mass communication. Advertisements contain about language, whether verbal and non-verbal. For that reason, advertisements can also analyze by language theories, like semiotic. Most television commercials portray the patriarchy of common perceptions where men make decisions for women and there is no place for gender equality. This work illustrates the analysis of the bold "liquid Dettol" advertisement in Indonesia that conveys a gender problem message. Semiotic analysis, qualitative, descriptive method, is used to analyze the signs associated with the message of gender issues, namely as high as the education of women, must be able to build their households, especially in comforting their children. In this research, researcher used the theory of Roland Barthes, through his semiotic theory to analyze gender myths in the ad. Myths can be analyzed through signs, which are contained in advertisements. In addition, the authors also use qualitative theories to analyze and describe this research.